2015
DOI: 10.7785/tcrt.2012.500392
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Passive Versus Active Scanning Proton Beams on Human Lung Epithelial Cells

Abstract: The goal was to characterize differences in cell response after exposure to active beam scanning (ABS) protons compared to a passive delivery system. Human lung epithelial (HLE) cells were evaluated at various locations along the proton depth dose profile. The dose delivered at the Bragg peak position was essentially identical (∼4 Gy) with the two techniques, but depth dose data showed that ABS resulted in lower doses at entry and more rapid drop-off after the peak. Average dose rates for the passive and ABS b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…Although, IL6 was not downregulated by proton radiation, it seemed like photons more strongly induce IL6 upregulation. Gridley et al previously compared transcription response to passively and actively modulated proton beams and found that IL6 was upregulated approximately twofold in a fibroblast cell line [26]. Thus, their finding also points toward IL6 being upregulated rather than downregulated by proton radiation.…”
Section: Discussionmentioning
confidence: 95%
“…Although, IL6 was not downregulated by proton radiation, it seemed like photons more strongly induce IL6 upregulation. Gridley et al previously compared transcription response to passively and actively modulated proton beams and found that IL6 was upregulated approximately twofold in a fibroblast cell line [26]. Thus, their finding also points toward IL6 being upregulated rather than downregulated by proton radiation.…”
Section: Discussionmentioning
confidence: 95%
“…Currently dosimetric calculations use a constant RBE of 1.1. Although the use of a constant RBE was judged to be acceptable in passive‐scattering proton therapies, this assumption resulted from the lack of biological input parameters and oversimplified the real situation, especially for IMPT . The problem of determining RBE values is complex and involves various factors including beam radiation quality (e.g., linear energy transfer [LET]), tissue type, physical dose, and biological endpoint .…”
Section: Introductionmentioning
confidence: 99%
“…Pencil beam scanning (PBS) is a fast-developing proton delivery technique offering improved conformal dose coverage of targets and reduced dose to organs at risk (OARs) 1,2 compared to the conventional photon-based radiotherapy. However, the relative biological effectiveness (RBE) of protons is to date poorly understood [3][4][5][6][7] due to its complex dependence on several factors including the linear energy transfer (LET), biological endpoint, tissue type, physical dose, 6,8 and the uncertainty of experimental results. [9][10][11][12][13][14] As a result, it is difficult to give an accurate estimate of proton RBE for clinical dose calculations.…”
Section: Introductionmentioning
confidence: 99%